Chronology of Gonadal Development in the Malayan Snail-eating Turtle Malayemys macrocephala - Pewphong, Rangsima (Zool Stud, 2020)
The snail-eating turtle, Malayemys macrocephala, is a common freshwater turtle that can be used as an animal model for developmental biology. However, a thorough investigation of its development is needed before this species can be used as a model. Thus, this study aimed to examine the gonadal development of M. macrocephala. Turtle eggs were collected from rice fields in Phra Nakhon Si Ayutthaya Province, Thailand, and transported to the laboratory. Eggs were incubated in microprocessor-controlled incubators and randomly dissected on a weekly basis to reveal the developing embryos, then their developmental stage was identified according to Yntema (1968). Primordial germ cells and gonad structure were processed through the paraffin method. Moreover, the dynamics of germ cell proliferation and apoptosis were examined by immunohistochemical detection of proliferating cell nuclear antigen (PCNA) and the terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL), respectively. Examination of the gonad revealed four main stages of gonadal development: (i) germ cell migration, (ii) genital ridge appearance, (iii) testicular formation, and (iv) ovarian formation. In the male turtle (incubated at 26°C), gonad developed into the testis with medullary sex cords starting at Yntema stage 17. In the female turtle (incubated at 32°C), these sex cords then degenerated, followed by cortical development into an ovarian structure starting at Yntema stage 19. Subsequently, testicular and ovarian development occurred independently, and distinct sex organs were apparent at Yntema stage 25. In addition, the presumptive testis showed germ cell proliferation in the medulla at Yntema stages 17, 19, and 25 and germ cell apoptosis in the cortex at Yntema stages 19 and 25. The presumptive ovary showed germ cell proliferation in the cortex at Yntema stages 19 and 25, and germ cell apoptosis in the medulla at Yntema stages 19 and 25